URGENSI PEMETAAN KEMAMPUAN DAN HAMBATAN SISWA MENGGUNAKAN PRE TEST-POST TEST DALAM PROGRAM TAHFIDZ: STUDY KASUS DI SD MUHAMMADIYAH PURWODININGRATAN - Subastia, Monica; Rahmi, Lailatul; Gunawan, Resky Nuralisa; Zafrullah, Zafrullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to see how much urgency there is in using pre-test and post-test as a tool to map students' abilities and obstacles in the Tahfidz Program through a case study at SD Muhammadiyah Purwodingratan. Students' abilities and obstacles are important factors that need to be known so that the tahfidz program is implemented according to their abilities and produces good competencies for students without making it difficult for students. The pre-test and post-test instruments were compiled based on the results of observations of the implementation of the tahfidz program in class 1 of SD Muhammadiyah Purwodingratan. The results of the study indicate that mapping students' abilities and obstacles is important to do so that the policies and models used are not wrong and make it difficult for students. Pre-test and post-test are effective tools in mapping students' abilities and obstacles in the tahfidz program. With this mapping, schools can make policies and teachers know the right models and methods to use in the tahfidz program so that the achievement of the tahfidz program increases